Tourism Intelligence: Analisis Data Geospasial Pembangunan Pariwisata Terintegrasi di Kawasan Dieng Plateau - Prayasta, I Gede Heprin; Lestari, Ni Gusti Putu Ayu Sri; Sweta, I Nyoman (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
The tourism industry in the Dieng Plateau region, Central Java, has great potential but has not been optimally managed. The lack of integration of available supporting facilities results in uneven development. This study aims to delineate and cluster tourist destinations according to the availability of infrastructure spread across the Dieng Plateau region. Geospatial POI data is analysed using the DBSCAN clustering technique to identify integration strategies. The results show that disparities in supporting facilities are found at several tourist destinations. Furthermore, the lack of variety of events other than the Dieng Culture Festival (DCF) is one area of improvement. This study delineated three development zones derived from the spatial distribution of tourism activities and supporting facilities, representing different stages of development. Targeted development strategies are proposed according to the characteristics and priorities of the clusters formed by involving relevant stakeholders.